Advances and trends in high-temperature modification–crystallization control detoxification of stainless steel slag - Xin ZHANG; Mei ZHANG; Min GUO (工程科学学报, 2023)
To date, the recycling technology of common solid waste (blast furnace iron slag) in the iron and steel industry has made important progress. However, persisting, stubborn solid waste problems urgently need to be solved. With the continuous growth of stainless steel production in China, the total amount of stainless steel slag has reached more than 10 million tons. This slag contains a lot of CaO, MgO, and SiO2, which are suitable building material additives. However, the harmful element chromium (Cr) in the slag and the dissolution characteristics of Cr6+ ions limit its large-scale application. For a long time, no effective, harmless disposal method has been available for Cr-containing slag, which brings great hidden danger to the environment. Given the characteristics of stainless steel slag, the current detoxification methods mainly include the solidification method, wet reduction, high-temperature ferrosilicon reduction, and high-temperature modification–crystallization control processes. Among these methods, high-temperature modification–crystallization control can promote Cr-containing spinel phase formation by adjusting steel slag compositions (e.g., basicity and oxidation-reduction properties) to improve the enrichment degree of Cr in the spinel phase. At the same time, by adjusting the slag cooling system (e.g., the quenching temperature and holding time) and reducing the slag viscosity, the nucleation and growth of the Cr-containing spinel phase can be improved, the precipitation amounts of the spinel phase are increased, and the occurrence probability of chromium in the matrix phase is reduced; thus, the detoxification of stainless steel slag can be achieved. Compared with the other three detoxification treatment methods, high-temperature modification–crystallization control has the advantages of a simple process, stable treatment effect, and large scale. In particular, solid wastes containing silicon, aluminum, and magnesium can be used as additives to adjust the composition of steel slag to realize a coordinated treatment of various solid wastes, which has very high economic value. In addition, using waste heat to modify steel slag directly after slag picking can substantially reduce energy consumption, should become one of the most promising harmless treatment approaches, and has recently attracted extensive attention. In this paper, the research progress of high-temperature modification and detoxification of stainless steel slag is reviewed according to its thermodynamic mechanism and crystallization kinetics principles. On the basis of the core problem of melt modification-selective crystallization, the methods and measures for improving the detoxification effect are emphasized. In addition, aiming at the existing problems in the high-temperature modification–crystallization control detoxification of stainless steel slag, development directions are proposed.